PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN KEMAMPUAN BELAJAR - Sasmi, Meri (2016)
Application of Realistic Mathematics Education Approach to Improve Learning Ability. One of the hopes in mathematics learning is that students active learning takes place and can understand the material presented well. The fact that happened contrary to the desired expectations. Mathematics Learning more passive, monotonous and boring. This article aims to improve the learning ability of students to the application of the PMR approach in teaching mathematics in grade III SD Laboratory Pilot UPI. The purpose of this study are: steps on implementation and improvement of student learning ability in class III Elementary Mathematics learning through the implementation of realistic mathematics learning approach. The method used was behavior class research and the result shows that there are enhancement learning process and student result. The average score of students in first cycle is 72,17, and the second cycle is 93,63 or as much as 100% students reaches a value above criteria mastery minimal. In general, this research can improve students' learning ability and can creates a more pleasant learning. ;---Salah satu harapan dalam pembelajaran matematika adalah berlangsungnya pembelajaran yang siswanya aktif serta dapat memahami materi yang disampaikan dengan baik. Kenyataan yang terjadi bertolak belakang dengan harapan yang diinginkan. Pembelajaran Matematika lebih cenderung pasif, monoton serta membosankan. Artikel ini bertujuan untuk meningkatkan kemampuan belajar siswa dengan penerapan pendekatan PMR dalam pembelajaran Matematika pada siswa kelas III SD Laboraturium Percontohan UPI. Tujuan penelitian ini adalah: mengetahui langkah-langkah pelaksanaan dan peningkatan kemampuan belajar siswa kelas III SD pada pembelajaran Matematika melalui implementasi pendekatan pembelajaran matematika realistik. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) dan hasil penelitian menunjukkan adanya peningkatan proses belajar dan hasil belajar siswa. Siklus I nilai rata-rata siswa 72,17 dan siklus II nilai rata-ratanya 93,63 atau sebanyak 100% siswa mencapai nilai diatas KKM. Secara umum, penelitian ini apat meningkatkan kemampuan belajar siswa serta dapat mencipatakan pembelajaran yang lebih menyenangkan.